The Lasting Impact of the Tuskegee Syphilis Study: COVID-19 Vaccination Hesitation among African Americans - Xiaolong Hou; Yang Jiao; Leilei Shen; Zhuo Chen (Global Labor Organization (GLO), 2024)
It is widely recognized that African Americans have a higher level of mistrust towards the medical and health care sector, which results in insufficient utilization of public health services, low participation in clinical research, and vaccination hesitancy. While the Tuskegee Syphilis Study has been identified as a key factor in this mistrust, its specific influence on COVID-19 vaccination uptake among African Americans remains unexplored. Our paper fills this research gap. Our results suggest that the difference in COVID-19 vaccination rates between communities with low and high proportions of Black residents decreases during the study period, but the gap persists. Notably, counties closer to Tuskegee exhibit a slower rate of progress in reducing the racial disparity in COVID-19 vaccination, indicating that the lingering mistrust stemming from the Tuskegee Study has contributed to unequal vaccination rates between African Americans and the rest of America.
Keywords: I1; N9; 330; Vaccination; COVID-19; Racial Disparity; Tuskegee